Botanical Characteristics of the Red Maple (Acer Rubrum) In Samarkand Region: Adaptation to Climate, Soil, and Flora - o’g’li, Baratov Kamol Urolboy; qizi, Kuchkarova Zarifa Donyorxon; Shuhratovich, Shernazarov Shavkat (American Journal of Biodiversity, 2025)
This article examines the botanical characteristics of the red maple (Acer rubrum) and its growth and development features under the climatic and soil conditions of the Samarkand region. The study highlights that red maple can adapt to different soils and moisture levels but faces challenges under prolonged drought, as well as summer climatic and soil stresses. The findings show that climatic and edaphic factors largely determine the distribution and survival of red maple in this environment. Overall, red maple is presented as a model for resilience and ecological responses in the conditions of Samarkand.